Rapid rEcognition of COrticosteRoiD resistant or sensitive Sepsis (RECORDS): study protocol for a multicentre, placebo-controlled, biomarker-guided, adaptive Bayesian design basket trial. Issue 3 (10th March 2023) - Fleuriet, Jérôme; Heming, Nicholas; Meziani, Ferhat; Reignier, Jean; Declerq, Pierre-Louis; Mercier, Emmanuelle; Muller, Grégoire; Colin, Gwenhaël; Monnet, Xavier; Robine, Adrien; Siami, Shidasp; Uhel, Fabrice; et al.
Abstract : Introduction: Corticosteroids affect variably survival in sepsis trials, suggesting heterogeneity in patients' response to corticosteroids. The RECORDS (Rapid rEcognition of COrticosteRoiD resistant or sensitive Sepsis) trial aimed at defining endotypes associated with adults with sepsis responsiveness to corticosteroids. Methods and analysis: RECORDS, a multicentre, placebo-controlled, biomarker-guided, adaptive Bayesian design basket trial, will randomly assign to a biomarker stratum 1800 adults with community-acquired pneumonia, vasopressor-dependent sepsis, septic shock or acute respiratory distress syndrome. In each stratum, patients will be randomly assigned to receive a 7-day course of hydrocortisone and fludrocortisone or their placebos. Patients with COVID-19 will be treated with a 10-day standard course of dexamethasone and randomised to fludrocortisone or its placebo. Primary outcome will be 90-day death or persistent organ dysfunction. Large simulation study will be performed across a range of plausible scenarios to foresee power to detect a 5%–10% absolute difference with corticosteroids. We will assess subset-by-treatment interaction by estimating in a Bayesian framework two quantities: (1) measure of influence, relying on the value of the estimation of corticosteroids' effect in each subset, and (2) measure of interaction. Ethics and dissemination: The protocol was approved by the Ethics Committee ( Comité de Protection des Personnes, Dijon, France), on 6 April 2020. Trial results will be disseminated at scientific conferences and results will be published in peer-reviewed journals. Trial registration number: ClinicalTrials.gov Registry (NCT04280497 ).